2015
DOI: 10.1186/s13099-015-0075-z
|View full text |Cite
|
Sign up to set email alerts
|

Survey of small intestinal and systemic immune responses following murine Arcobacter butzleri infection

Abstract: BackgroundArcobacter (A.) butzleri has been described as causative agent for sporadic cases of human gastroenteritis with abdominal pain and acute or prolonged watery diarrhea. In vitro studies revealed distinct adhesive, invasive and cytotoxic properties of A. butzleri. Information about the underlying immunopathological mechanisms of infection in vivo, however, are scarce. The aim of this study was to investigate the immunopathological properties of two different A.butzleri strains in a well-established muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…After oral administration of A. butzleri, the bacteria readily colonize the murine intestinal tract. However, infected mice did not show any overt clinical signs, the bacteria not only induced intestinal immune responses but also systemic immune responses in extra-intestinal places depending on the strain and time course of infection Heimesaat et al 2015a). These immune responses were TLR-4 dependent recognized by LOS and LPS derived from the cell walls of Gramnegative bacteria in gnotobiotic IL-10 -/-mice lacking TLR-4 with less pronounced intestinal and systemic immune responses Heimesaat et al 2015b;Heimesaat et al 2016).…”
Section: Disease In Animals Caused By Arcobactersmentioning
confidence: 99%
See 1 more Smart Citation
“…After oral administration of A. butzleri, the bacteria readily colonize the murine intestinal tract. However, infected mice did not show any overt clinical signs, the bacteria not only induced intestinal immune responses but also systemic immune responses in extra-intestinal places depending on the strain and time course of infection Heimesaat et al 2015a). These immune responses were TLR-4 dependent recognized by LOS and LPS derived from the cell walls of Gramnegative bacteria in gnotobiotic IL-10 -/-mice lacking TLR-4 with less pronounced intestinal and systemic immune responses Heimesaat et al 2015b;Heimesaat et al 2016).…”
Section: Disease In Animals Caused By Arcobactersmentioning
confidence: 99%
“…However, infected mice did not show any overt clinical signs, the bacteria not only induced intestinal immune responses but also systemic immune responses in extra-intestinal places depending on the strain and time course of infection Heimesaat et al 2015a). These immune responses were TLR-4 dependent recognized by LOS and LPS derived from the cell walls of Gramnegative bacteria in gnotobiotic IL-10 -/-mice lacking TLR-4 with less pronounced intestinal and systemic immune responses Heimesaat et al 2015b;Heimesaat et al 2016). The mucin-2 is a pivotal constituent of the intestinal mucosa providing first line defense against intestinal pathogens (Strugala et al 2003) and was downregulated in the colon, but not in the ileum of A. butzleri infected mice (G€ olz et al 2016b;Heimesaat et al 2016).…”
Section: Disease In Animals Caused By Arcobactersmentioning
confidence: 99%
“…The A. butzleri reference strain CCUG 30485 was initially isolated from a fecal sample derived from a diarrheal patient [ 23 ], whereas the C1 strain was isolated from fresh chicken meat [ 10 ]. Both A. butzleri strains were grown on Karmali-Agar (Oxoid, Wesel, Germany) for 2 days at 37 °C under microaerobic conditions using CampyGen gas packs (Oxoid) as described earlier [ 20 , 21 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…We have recently shown that, upon peroral A. butzleri infection, gnotobiotic IL-10 –/– mice with a depleted commensal microbiota following broad-spectrum antibiotic treatment [ 19 ] could be stably infected by the bacterium and displayed significant small and large intestinal pro-inflammatory immune responses [ 20 , 21 ]. Remarkably, infection-induced sequelae were not restricted to the intestinal tract, given that even systemic inflammatory responses could be observed in infected mice.…”
Section: Introductionmentioning
confidence: 99%
“…Given that C. jejuni and A. butzleri are taxonomically related, we very recently applied the gnotobiotic IL-10 –/– mouse model to determine the pathogenic potential of A. butzleri and to investigate bacterial–host interactions in vivo . The results indicate that, upon peroral A. butzleri infection, mice could be stably colonized by the respective strains and displayed significant small and large intestinal as well as extraintestinal and systemic inflammatory responses [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%